Organ Transplant Agreement from Donor to Kidney Failure Receptor as Stated in Notarial Deed (Case Study: Central Jakarta District Court Decision Number: 587/Pid.B/2019/Pn.Jkt.Pst) - Claudia Yolanda Pricilla; Tjempaka Tjempaka (Journal of Social Research, 2023)
Health is one of the basic human needs, in addition to clothing, food and shelter. Without a healthy life, human life becomes meaningless, because with illness, humans may not be able to carry out daily activities properly. The purpose of this study is to review and analyze the procedures and mechanisms of human organ transplantation until it is stated in a notary deed. In this writing, the research method that the author uses is the normative legal research method. Regulation on organ transplantation in Indonesia is regulated in Law Number 36 of 2009 concerning Health in Articles 64-65 concerning organ transplantation. In terms of reducing the illegal trafficking or buying and selling of human organs and to legalize human organ donation, an authentic deed authorized by a notary is required. The kidney transplant agreement in question has no legal force. In other words, a contract without a legal cause would be null and void.